Pengaruh Bauran Pemasaran 4D Terhadap Keputusan Pembelian Pengguna GoFood - Intana Wahyu Putri; Esti Dwi Rahmawati; Indra Hastuti (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
Changes in technological advances and increased Internet penetration have led to changes in consumer purchases. The study aims to analyze “The impact of 4D marketing mix on GoFood consumer purchasing decisions in Surakarta”. The population in this study is the entire consumer in Surakarta City who has used the service of messaging between GoFood and has made a purchase. The study uses purposive sampling as a sample determination technique and the number of samples in this study is 100 respondents. Variables In this study there are 5 variables to be studied, namely the independent variables consisting of Disruption (X1), Digitalization (X2), De-Siloage (X3), and Diffusion (X4), as well as Purchase Decision (Y) as dependent variables. The results of this study show that the variables disruption(X1), de-siloage(X3) and diffusion(X4) have a positive and significant influence on the Purchasing Decision of GoFood Application Users in Surakarta, whereas the variable digitalization(X2) has a negative and significant impact on the Buying Decisions of Gofood Application users in Surakarta.